Impact of changes in perinatal care on bronchopulmonary dysplasia: an overview of the last two decades - Azevedo, A (2017)
Objective: To compare the clinical approach and outcomes of bronchopulmonary dysplasia (BPD) patients in the last two decades (1996-2005 vs 2006-2015) in a neonatal intensive care unit. Methods: Out of 1,196 admissions of very low birth weight and/or less than 32 weeks of gestational age infants, 96 had BPD and were dichotomized into two groups according to the year of birth (1996-2005 and 2006-2015). Their clinical data were studied and conclusions were drawn about their morbidity and mortality. Results: There was a decrease in mortality (23.3% vs. 14.4%, p < 0.001) and in BPD prevalence (9.7% vs 6.1%, p = 0.023); in the delivery room, early nasal continuous positive airways pressure (nCPAP) was used in 41.2% vs 1.6%, p < 0.001 and tracheal intubation in 70.6% vs 96.8%, p < 0.001. We observed an increase on the duration of non-invasive ventilation (nCPAP, 22.5 vs 45.5 days, p < 0.001) and a decrease of invasive ventilation (39.5 vs 20 days, p = 0.013) from the first to the second period. Conclusions: Improvement in perinatal and neonatal intensive care practices, namely the use of non-invasive methods of mechanical ventilation implemented in the last years, probably contributed to the better evolution of preterm infants with BPD.